Reciprocal Effects of Silicon Supply and Endophytes on Silicon Accumulation and Epichloë Colonization in Grasses - Cibils-Stewart, Ximena; Powell, Jeff R.; Popay, Alison Jean; Lattanzi, Fernando Alfredo; Hartley, Sue Elaine; Johnson, Scott Nicholas (Frontiers in Plant Science, 2020)
Cool season grasses associate asymptomatically with foliar Epichloë endophytic fungi in a symbiosis where Epichloë spp. protects the plant from a number of biotic and abiotic stresses. Furthermore, many grass species can accumulate large quantities of silicon (Si), which also alleviates a similar range of stresses. While Epichloë endophytes may improve uptake of minerals and nutrients, their impact on Si is largely unknown. Likewise, the effect of Si availability on Epichloë colonization remains untested. To assess the bidirectional relationship, we grew tall fescue (Festuca arundinacea) and perennial ryegrass (Lolium perenne) hydroponically with or without Si. Grasses were associated with five different Epichloë endophyte strains (tall fescue: AR584 or wild type; perennial ryegrass: AR37, AR1, or wild type) or as Epichloë-free controls. Reciprocally beneficial effects were observed for tall fescue associations. Specifically, Epichloë presence increased Si concentration in the foliage of tall fescue by at least 31%, regardless of endophyte strain. In perennial ryegrass, an increase in foliar Si was observed only for plants associated with the AR37. Epichloë promotion of Si was (i) independent of responses in plant growth, and (ii) positively correlated with endophyte colonization, which lends support to an endophyte effect independent of their impacts on root growth. Moreover, Epichloë colonization in tall fescue increased by more than 60% in the presence of silicon; however, this was not observed in perennial ryegrass. The reciprocal benefits of Epichloë-endophytes and foliar Si accumulation reported here, especially for tall fescue, might further increase grass tolerance to stress.